Analisis Peran Media Interaktif Berbasis PowerPoint dalam Meningkatkan Keterlibatan Belajar Siswa di Madrasah Ibtidaiyah (Jurnal PGSD Universitas Lamappapoleonro, 2025)
This study aims to analyze the role of PowerPoint-based interactive media in increasing student engagement in learning at Madrasah Ibtidaiyah. PowerPoint-based interactive media was chosen because of its ability to present learning materials visually, audibly, and dynamically, which is believed to attract students' attention and increase their participation in the learning process. The research method used was a qualitative approach with data collection techniques through observation, interviews, and documentation of fifth-grade students and teachers at an elementary school in Soppeng Regency. The results of the study indicate that the use of interactive PowerPoint equipped with animations, quizzes, images, and sounds can increase students' focus, enthusiasm, and activity in learning activities. Teachers also found it easier to present complex material in a simpler and more engaging manner. Additionally, students' cognitive, affective, and psychomotor involvement appeared to increase compared to conventional learning methods. Thus, interactive PowerPoint-based media has been proven to positively contribute to enhancing student engagement in learning at Madrasah Ibtidaiyah. This study recommends training in the use of digital media for teachers to optimize the utilization of technology in teaching and learning activities.